THE EFFICACY OF TOPICAL CLINDAMYCIN GEL ON SEVERITY DEGREE OF ACNE VULGARIS AMONG FEMALE COLLEGE STUDENTS - Hapsari, Rani Puspita; Widayati, Retno Indar; Afriliana, Liza; Hadi, Purnomo (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Acne vulgaris is a chronic inflammatory disease in the pilosebaceous follicle of the skin as the result of Propionibacterium acnes colonization. Clindamycin is an antibiotic that is effective against most gram-positive anaerobic bacteria such as the strain of Â Propionibacterium sp. Clindamycin in topical form inhibits P. acnes lipase enzyme resulting in the decrease of free fatty acid on the skin surface and the decrease of the Propionibacterium acnes population. Â Aim: To know the effect of topical clindamycin gel application on the severity degree of acne vulgaris among female college students of Diponegoro University. Methods: The study has done on 34 female college students of Diponegoro University who were diagnosed with Acne Vulgaris. All of the subjects underwent a face skin examination where the acne lesions were counted before and after the treatment. The treatment given was the application of clindamycin topical gel once a day for four weeks. The counted acne lesions were classified into the severity degree of acne vulgaris by Plewig and Kligman. The study compared the severity degree of acne vulgaris before and after the treatment. Statistical analysis of this study used the Wilcoxon test. Result: The result of pre and post-treatment data showed a significant decrease in the severity degree of acne vulgaris after the treatment application (p=0.000). The decrease of severity degree was marked by the decrease of acne lesion count after having four weeks of treatment. This significant result indicated an effective recovery of acne vulgaris after being given the treatment of topical clindamycin. The antibiotic and anti-inflammation effects of clindamycin were discovered effectively healing the lesions of acne vulgaris, therefore, decreasing its severity. Conclusion: Topical clindamycin can effectively reduce the severity degree of acne vulgaris among female college students of Diponegoro University.